Estimating the Need for Sedation in Patients with Dental Anxiety and Medical Complexities Reporting to Tertiary Care Dental Hospital Using the IOSN Tool - Beenish Abbas; Ayesha Maqsood; Syeda Rabia Rahat Geelani; Madeeha Sattar; Majida Rahim; Zohaib Khurshid (International Journal of Dentistry)
Objectives. To provide consistent method for assessment of sedation need among patients undergoing dental treatment based on specific risk factors that is dental anxiety, medical status, and treatment complexity of needed dental treatment using IOSN (indication of sedation need) tool for assisting the clinician in decision making process. Methods. A total of 237 patients aged ≥12, ASA I and II were enrolled in the study. A structured questionnaire comprising of three sections was distributed among the participants. Section 1 comprises details about age, gender, literacy level, occupation, monthly income, and previous dental treatment history. Section 2 is based on Modified Dental Anxiety Scale which is a questionnaire comprising of five questions ranging from “not anxious” to “extremely anxious.” The third section was based on using the IOSN tool comprising three components: MDAS (Modified Dental Anxiety Scale) rank score, Systemic Health (ASA status) rank score, and treatment complexity rank scores. The total of three scores was then computed to determine the total rank score which suggested the sedation need. History of past traumatic dental experiences was also inquired from each patient. Results. A total of 237 patients aged ≥12, ASA I and II were enrolled in the study, out of which 56.1% were female. Statistical analysis was conducted by using the IBM SPSS Statistics 23 software. Based on the MDAS score, 47/237 (19.8%) participants were found to be highly anxious related to dental procedures. 34.6% of the participants showed to have a high sedation need while performing a dental procedure. The sedation need was found to be significantly associated with the female gender with a significant p value of p=0.016, higher education status p=0.016, and history of previous traumatic dental experience p<0.001. Conclusion. A simple assessment tool can enable clinicians in their decision making to identify patients in need for dental treatment under sedation based on patient-specific risk factors such as past traumatic dental experiences. Need for sedation can be assessed by information on patient anxiety level towards dental treatment, medical history, and complexity of planned dental treatment. The IOSN tool is a simple and quick assessment tool that can be applied for preprocedural assessment of sedation need for dental treatment.